Localization of Global Environmental Norm in Lamalera Whaling Tradition - Putri, Penny Kurnia; Nugraha, Anak Agung Bagus Surya Widya (Global Strategis, 2026)
This research aims to examine the power relations among actors in the process of localizing global environmental norms and species protection, which clashes with traditional values.  The research uses a qualitative approach, drawing on primary data collected through structured discussions, in-depth interviews, and field observations. The analysis focuses on norm localization stages, framed within global environmentalism perspective, contextualized through aboriginal subsistence whaling and communal culture concepts. The findings suggest that the emergence of local resistance is a phase of norm localization theory that offers a framework for negotiating shared understandings. The tension between whaling tradition and marine conservation norms can be mediated through the alignment of global environmental objectives with subsistence-based cultural practices. The whaling tradition in Lamalera may be permitted, provided it adheres to subsistence-based criteria, including hunting periods, cetacean population, types of tools, and local consumptions. This recognition has implications for the exclusion of Lamalera waters from conservation zoning. Through mutual compromise, modified norms are then implemented via customary, local, and national regulatory mechanisms. Furthermore, Indonesian government has enacted Leva Nuang as a national intangible cultural heritage, affirming the legitimacy of Lamalera's traditions within a broader framework of sustainable cultural practices. Keywords: Conservation, Environmentalism, Lamalera, Norm-localization, Whaling Penelitian ini bertujuan untuk menganalisis relasi kuasa antaraktor dalam proses lokalisasi norma lingkungan dan pelindungan spesies yang berbenturan dengan norma tradisional. Pendekatan penelitian dilakukan secara kualitatif dan didukung oleh data primer, berupa diskusi terstruktur, wawancara mendalam, serta observasi lapangan. Pembahasan berfokus pada dinamika tahap lokalisasi norma yang dikaji secara teoritis melalui perspektif environmentalisme global, serta didukung oleh konsep aboriginal subsistence whaling dan konsep budaya komunal. Hasil penelitian menunjukkan bahwa resistensi masyarakat yang muncul merupakan bagian proses lokalisasi norma untuk menciptakan ruang negosiasi. Benturan antara norma perburuan paus dengan norma konservasi laut kemudian dapat dikompromikan antarpihak melalui keselarasan kajian lingkungan global dan budaya subsisten. Tradisi masyarakat Lamalera dapat dilakukan selama praktiknya tetap sesuai dengan variabel kajian subsisten, meliputi periode waktu, kondisi mamalia laut, jenis alat yang digunakan, dan pola distribusi hasil. Pengakuan budaya subsisten atas tradisi ini berbanding lurus dengan kompromi pembebasan zona konservasi perairan. Masing-masing pihak mengompromikan normanya sehingga tercipta modifikasi norma yang disepakati dan dijalankan bersama melalui penerapan aturan atau sanksi adat, lokal, maupun nasional. Untuk menjaga komitmen sekaligus melestarikan budaya setempat, pemerintah Indonesia juga mengeluarkan kebijakan yang menetapkan Leva Nuang sebagai warisan budaya tak benda nasional. Kata-kata kunci: Environmentalisme, Konservasi, Lamalera, Lokalisasi Norma, Perburuan Paus